2008
DOI: 10.2337/db07-1579
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Oxidative DNA Damage in Diabetes

Abstract: OBJECTIVE-To investigate potential mechanisms of oxidative DNA damage in a rat model of type 1 diabetes and in murine proximal tubular epithelial cells and primary culture of rat proximal tubular epithelial cells. Akt and tuberin, levels, and 8-oxoG-DNA glycosylase (OGG1) expression were measured in kidney cortical tissue of control and type 1 diabetic animals and in proximal tubular cells incubated with normal or high glucose. RESEARCH DESIGN AND METHODS-Phosphorylation ofRESULTS-In the renal cortex of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 51 publications
9
90
1
1
Order By: Relevance
“…In a previous study, Kang et al (2009) demonstrated that OGG1 induced this via the activation of the PI3K/Akt pathway. In contrast, Simone et al (2008) found that inhibition of PI3K/Akt reversed the OGG1 expression downregulated by high glucose treatment in the renal cortex of diabetic rats. Therefore, the relationships of DNA-PKcs, Ku heterodimer, and OGG1 to PI3K/Akt need to be elucidated in future.…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study, Kang et al (2009) demonstrated that OGG1 induced this via the activation of the PI3K/Akt pathway. In contrast, Simone et al (2008) found that inhibition of PI3K/Akt reversed the OGG1 expression downregulated by high glucose treatment in the renal cortex of diabetic rats. Therefore, the relationships of DNA-PKcs, Ku heterodimer, and OGG1 to PI3K/Akt need to be elucidated in future.…”
Section: Discussionmentioning
confidence: 79%
“…Prolonged exposure (1-13 d) of proximal tubular epithelial cells to hyperglycemic environment has been shown to inhibit cell proliferation and induce growth arrest or cellular MINIREVIEWS apoptosis [8][9][10][11][12] . These cellular effects are caused by the activation of a network of intracellular signaling pathways and include the phosphatidylinostiol 3 kinase (PI3 kinase)/adams kara taylor (AKT) signaling pathway [13] . Activation of PI3 kinase and phosphorylation of serine/threonine kinase AKT/protein kinase B (PKB) by insulin, insulin like growth factors in human embryonic 293 (HEK-293) and HeLa cells lead to inactivation of tuberin by phosphorylating at Ser939, Ser1086/1088 and Thr1422 [14,15] .…”
Section: Apoptosismentioning
confidence: 99%
“…Glucose serves as an energy source in virtually all eukaryotic cells. A high concentration of glucose increases the metabolic input into cells and consequently induces oxidative stress via ROS production, thereby inducing DNA, protein, and lipid damage, causing premature senescence (Mortuza, Chen, Feng, Sen, & Chakrabarti, 2013; Simone, Gorin, Velagapudi, Abboud, & Habib, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…AKT also activates the mechanistic target of rapamycin (mTOR) and induces cellular senescence (Johnson, Rabinovitch, & Kaeberlein, 2013). Furthermore, high glucose levels stimulate protein synthesis and induce ROS production by AKT phosphorylation (Sheu, Ho, Chao, Kuo, & Liu, 2004; Simone et al, 2008). …”
Section: Introductionmentioning
confidence: 99%